EMERGENCY PATIENTS RIGHTS AND DIGNITY IN BULGARIA - Desislava Todorova; Svetoslav Garov; Tsvetelina Mihailova (Peytchinski Publishing, 2017)
In addition to the emergency medical services the victims of various disasters and accidents need to keep their dignity as human beings. Dignity is a term used in morals and ethics to designate that people have the right to be respected and treated ethically. Providers of emergency medical services perform their activities in compliance with the rules of good medical practices while keeping professional secrecy and observing patient rights. Patient rights and in particular moral rights ensure respect for patients' lives and dignity in the health care system. The aim of the research is to study the ethical dilemma of saving patients' lives and protecting their dignity in cases of emergency. The purpose of the survey is to study the medical, ethical and legal aspects of the issue. A documentary method of collection data from scientific sources is used with regard to the different aspects of the topic. In a number of cases during their routine medical practice, especially in emergencies, medical experts have to make their choice of medical behavior - whether it has to comply with ethics or law. Making the right decision and choice of behavior depends on the moral values, professional training, knowledge of legal requirements and personal qualities of the relevant medical professional. One should always take into account that protecting victims' dignity is especially important in emergencies when they feel most vulnerable.